Pluralisme Hukum dan Keadilan Gender Dalam Penetapan Nafkah Istri di Indonesia - Sarah Sarah; M Adi Saputra; Firdaus Akbar; Syahriati Fakhriah (Universitas Semarang, 2025)
This study examines how legal pluralism shapes the determination of spousal maintenance and the protection of wives’ rights in Indonesia from a gender justice perspective. The coexistence of Islamic law, customary law, and state law often produces normative overlap and inconsistent judicial practices, which in turn weaken women’s economic protection, particularly after divorce. Existing studies tend to address these legal systems separately or adopt a purely descriptive approach, leaving a gap in integrative and evaluative analysis grounded in substantive justice. Employing a normative juridical method with statutory, conceptual, and comparative approaches, this research analyzes Law Number 1 of 1974 on Marriage, the Compilation of Islamic Law, and selected religious court decisions concerning post-divorce maintenance. The findings reveal that gender injustice persists through biased interpretations of husbands’ maintenance obligations, the influence of patriarchal customary norms that obscure individual responsibility, and disparities in judicial reasoning across regions. This study contributes originality by operationalizing maqashid al-sharia, particularly the principles of protection of life (hifz al-nafs) and protection of property (hifz al-mal), as an evaluative framework for assessing gender justice within a plural legal order. The study argues that integrating maqashid al-sharia with gender-sensitive legal interpretation is essential for reconstructing Indonesian family law toward greater legal certainty and substantive justice for wives. Penelitian ini mengkaji pengaruh pluralisme hukum terhadap penetapan nafkah dan perlindungan hak istri di Indonesia dari perspektif keadilan gender. Koeksistensi hukum Islam, hukum adat, dan hukum negara kerap melahirkan tumpang tindih norma serta ketidakkonsistenan praktik peradilan, yang berdampak pada lemahnya perlindungan hak ekonomi perempuan, khususnya pasca perceraian. Penelitian terdahulu umumnya masih bersifat parsial atau deskriptif, sehingga belum mengintegrasikan ketiga sistem hukum tersebut dalam kerangka evaluasi keadilan substantif. Dengan menggunakan metode penelitian hukum normatif yuridis melalui pendekatan perundang-undangan, konseptual, dan komparatif, penelitian ini menganalisis Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, Kompilasi Hukum Islam, serta sejumlah putusan pengadilan agama terkait nafkah pasca perceraian. Hasil penelitian menunjukkan bahwa ketidakadilan gender termanifestasi dalam bias penafsiran kewajiban nafkah suami, dominasi norma adat yang patriarkal, serta perbedaan pertimbangan hakim antarwilayah. Kebaruan penelitian ini terletak pada pemanfaatan maqashid syariah, khususnya prinsip perlindungan jiwa (hifz al-nafs) dan perlindungan harta (hifz al-mal), sebagai kerangka evaluatif operasional untuk menilai keadilan gender dalam sistem hukum pluralistik. Penelitian ini menegaskan pentingnya integrasi maqashid syariah dan perspektif keadilan gender dalam rekonstruksi hukum keluarga guna mewujudkan kepastian hukum dan keadilan substantif bagi istri.